Kinetics and Thermodynamic Parameters of Coffee Senna Seed (Senna occidentalis) Using Degradation Data from Roasting - Lawan, Muhammad Zannah; Muhammad, Idris Misau; Ahmed, Isah Saeed; Olu, Olubajo Olumide; Yusuf, Abdulkarim Abdulwadud; Maryam, Ibrahim (Mikailalsys Journal of Advanced Engineering International, 2025)
Coffee Senna Seeds (CSS) have demonstrated potential as medicinal substitutes, warranting further investigation into their thermal stability for industrial applications. This study aims to establish the kinetic and thermodynamic parameters governing the thermal degradation of bioactive compounds in CSS across a temperature range of 100°C to 200°C and exposure durations of 5 to 30 minutes. Phytochemicals including cardiac glycosides, anthraquinones, phenols, flavonoids, saponins, steroids, alkaloids, terpenoids, tannins, and glycosides were analyzed to determine degradation profiles. FTIR and UV-Vis spectrophotometric analyses confirmed the decomposition of anti-nutritional components such as anthraquinones, while beneficial compounds like phenols, flavonoids, and saponins remained largely intact. Kinetic modeling indicated that the degradation followed a volume contraction mechanism, with high R² values (0.9804–0.9915) validating model fit. The low reaction order (0.28–0.397) suggests a diffusion-controlled process, while varying conversion factors (α) reflected complex internal thermal dynamics within the seed matrix. Thermodynamic evaluation revealed the degradation process to be endothermic and non-spontaneous, with enthalpy (ΔH) values decreasing from 1585.90 to 754.50 kJ/mol and Gibbs free energy (ΔG) increasing from 102.92 to 130.18 kJ/mol as temperature rose. Negative entropy (ΔS) values, approximately −271.5 kJ/K, suggest a more ordered transition state, likely due to structural reorganization during roasting. Activation energy estimates ranged from 1589 to 758 kJ/mol, showing a decreasing trend with temperature, indicative of improved reaction feasibility at higher thermal inputs. These findings enhance understanding of CSS thermal behavior, supporting its detoxification and safer utilization in industrial processing.